The Political Economy of EU Climate and Energy Policies in Central and Eastern Europe Revisited: Shifting Coalitions and Prospects for Clean Energy Transitions - Ćetković, Stefan (2019)
The countries of Central and Eastern Europe (CEE) have commonly been regarded as climate and energy policy laggards blocking more ambitious EU decarbonization targets. Although recent literature has increasingly acknowledged the differences in national positions on energy and climate issues among these states, there has been little comprehensive evidence about their positioning on EU climate and energy policies and the domestic interests which shape government preferences. The article addresses this gap by tracing the voting behavior of six CEE countries (Poland, Hungary, Czech Republic, Slovakia, Bulgaria, and Romania) on EU energy-related legislation in the Council of Ministers between 2007–2018. The article shows that the contestation of energy policies, particularly of climate-related legislation, in the Council of Ministers has increased over time and that these six CEE countries have indeed most often objected to the adoption of EU legislation. The CEE states do not, however, have a common regional positioning on all EU energy policies. Voting coalitions among the six CEE countries differ substantially across energy policy areas. The lack of a common regional position and changing national preferences have enabled the adoption of a relatively ambitious EU Energy and Climate Package for 2030. The differences in national voting patterns are explained by the evolving interests and the ability of key domestic political and economic actors to adapt to and explore benefits from the ever-expanding EU energy and climate policies.